Effect of eliminating CD4-count thresholds on HIV treatment initiation in South Africa: an empirical modeling study - Bor, Jacob; Bärnighausen, Till (PLOS ONE, 2017)
Background: The World Health Organization recommends initiating antiretroviral therapy (ART) regardless of CD4 count. We assessed the effect of ART eligibility on treatment uptake and simulated the impact of WHO’s recommendations in South Africa. Methods We conducted an empirical analysis of cohort data using a regression discontinuity design, and then used this model for policy simulation. We enrolled all patients (n = 19,279) diagnosed with HIV between August 2011 and December 2013 in the Hlabisa HIV Treatment and Care Programme in rural South Africa. Patients were ART-eligible with CD4<350 cells/mm3 or Stage III/IV illness. We estimated: (1) distribution of first CD4 counts in 2013; (2) probability of initiating ART ≤6 months of HIV diagnosis under existing criteria at each CD4 count; (3) probability of initiating ART by CD4 count if thresholds were eliminated; and (4) number of expected new initiators if South Africa eliminates thresholds. Findings In 2013, 38.9% of patients diagnosed had a CD4 count ≥500. 8.0% of these patients initiated even without eligible CD4 counts. If CD4 criteria were eliminated, we project that an additional 19.2% of patients with CD4 ≥500 would initiate ART; 72.8% would not initiate ART despite being eligible. Eliminating CD4 criteria would increase the number starting ART by 26.7%. If these numbers hold nationally, this would represent an additional 164,000 initiators per year, a 5.2% increase in patients receiving ART and 5.3% increase in programme costs. Conclusions Removing CD4 criteria alone will modestly increase timely uptake of ART. However, our results suggest the majority of newly-eligible patients will not initiate. Improved testing, linkage, and initiation procedures are needed to achieve 90-90-90 targets.
Gesehen am 12.04.2018